Risk factors in Islamic green finance and a corporate solution - Al-Shaghdari, Fahd Mohammed Obad; Sharofiddin, Ashurov; Zakariyah, Habeebullah (Routledge (Taylor & Francis Group), 2024)
The perceived high risks of green-related projects are frequently highlighted by investors, industry players and policymakers as one of the causes leading to the setback growth of environmentally friendly businesses in developing nations, including Malaysia. Therefore, it is essential that these risk factors be identified and assessed thoroughly so that investors, industry players and policymakers can tackle these risks by implementing appropriate risk management and mitigation strategies. The present study aims to conduct a bibliometric analysis to explore the risk factors associated with Islamic green financing (IGF) and provide directions for potential future research. In the present study, the use of the bibliometric analytical technique was applied for exploring the risk factors involved in IGF. A total of 590 studies was collected from the research published in the Scopus and Dimensions.ai databases during the period 2010–2023 (October). The analysis of the selected articles was conducted via RStudio software. Through applying the bibliometric technique, the analysis elucidates the distinct risk categories pertaining to IGF. Those risks can be categorised into six distinct types, namely: environmental risk, regulatory risk, geopolitical risk, credit provision risk, pandemic risk, and spillover effect risk. The findings of this research will enlighten industry players, practitioners, investors and policymakers to gain in-depth consciousness on the risk factors associated with IGF for implementing appropriate risk management and mitigation measures to ensure the sustainability and compliance of green projects. This study contributes to the literature on IGF and opens new avenues for research in the field.